Struggling the Islamic State in Austral Africa: The SADC military intervention in Cabo Delgado (Mozambique) and its limits - Bussotti, Luca; Coimbra, Ermenegildo Júlio (Frontiers in Political Science, 2023)
This article analyses how SADC (Southern Africa Development Community) faced the threat of Islamic terrorism in one of its member states, Mozambique, since October 2017. This research is focused on the SADC strategy for counter-terrorism, having as its main perspective the military intervention, in a permanent dialogue with the political level of decision. The difficulties in organizing the military intervention in Mozambique by SADC demonstrated a lack of “Sadcnesses” or a common spirit and vision within this organization. In addition, the presence of many other international players on the field runs the risks of turning the conflict into an international clash between the West, led by the United States, and Islamic radicalism, in Mozambique present with Al-Shabaab and ISIS. The results of the SAMIM (SADC Mission in Mozambique) operation have not been satisfactory, and Mozambican people continue to be threatened by the incursions of well-armed and trained terrorist groups. This study used a qualitative approach based on a bibliographical as well as documental analysis of SADC documents and declarations. A comparative perspective with other African cases of a significant presence of terroristic groups helped the authors to better understand the jihadist attacks in Mozambique as well as the merely military approach to fight them.